2021
DOI: 10.1159/000519867
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Based on Plasma Biomarkers for the Phase 3 CELESTIAL Trial of Cabozantinib versus Placebo in Advanced Hepatocellular Carcinoma

Abstract: <b><i>Introduction:</i></b> Cabozantinib, an inhibitor of MET, AXL, and VEGF receptors, significantly improved overall survival (OS) and progression-free survival (PFS) versus placebo in patients with previously treated advanced hepatocellular carcinoma (HCC). In this exploratory analysis, outcomes were evaluated according to plasma biomarker levels. <b><i>Methods:</i></b> Baseline plasma levels were evaluated for MET, AXL, VEGFR2, HGF, GAS6, VEGF-A, PlGF, IL-8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In addition, as there is no established biomarker for the selection of therapeutic agents in HCC except AFP for ramucirumab, further efforts are required to define additional specific biomarkers for the prediction of each agent’s efficacy or toxicity. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, as there is no established biomarker for the selection of therapeutic agents in HCC except AFP for ramucirumab, further efforts are required to define additional specific biomarkers for the prediction of each agent’s efficacy or toxicity. 33 …”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68][69][70][71][94][95][96][97] Further circulating biomarkers, including MKIs targets, their ligands, and other plasma proteins, mainly with a role in inflammation/HCC pathogenesis were found to be prognostic and sometimes predictive in retrospective analyses of the SHARP, REFLECT, RESORCE, and CELESTIAL trials. 95,[100][101][102] However, they were not evaluated as biomarkers of response, and the non-homogenous significance across different studies and treatment arms, the lack of established cut-offs and uniform protocols for their measurement, and the rather intricate process required for their analysis limit further validation and make their use not yet feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CELESTIAL trial showed that a better prognosis during treatment with Cabozantinib was correlated with low levels of MET, GAS6, HGF, ANG2, VEGF-A, Interleukin (IL)-8, and high levels of insulin-like growth factor 1 in serum. However, these data have yet to be confirmed in clinical practice [ 75 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%